Arts-Based Research Approaches to Studying Mechanisms of Change in the Creative Arts Therapies - Gerber, Nancy; Bryl, Karolina; Potvin, Noah; Blank, Carol Ann (Frontiers in Psychology, 2018)
The purpose of this preliminary qualitative research study is to explore the role and function of multiple dynamic interactive aesthetic and intersubjective phenomena in the creative arts therapies process relative to transformation in perception, behavior, relationship, and well-being. A group of doctoral students and faculty studied these phenomena in an analogous creative arts therapies laboratory context using a method called Intrinsic Arts-Based Research. Intrinsic Arts-Based Research is a systematic study of psychological, emotional, relational, and arts-based phenomena, parallel to those emergent in the creative arts therapies, using individual and collective intrinsic immersive and reflective experience in combination with qualitative and arts-based research methods. Our primary goal was to simulate the creative arts therapies experience in order to identify, document, and describe the complex transformative phenomena that occur at the nexus of arts-based expression, reflection, and relationships in the arts therapies. For the purposes of this paper transformation is defined as “ . . . . a significant reconfiguration of perception and thought resulting in the lessening of psychic restraint and pain, allowing for the emergence of new psychological perspectives that contribute to living a more creative life” (Gerber et al. 2012, 45). Through a deductive thematic analysis of written accounts of these simulated creative arts therapies experiences by participant/researchers in the laboratory we identified three primary dynamic and interactive broad constructs that together, with more specific modifying themes, might account for and describe change within the creative arts therapies. These broad dynamic interactive themes are: ruptures, resolutions, and transformation; relationship and intersubjectivity; and, arts-based expressive processes. The more specific modifying themes include dialectical rupture and resolution, relational attunements and ruptures, imaginational flow, transcendence and ruptures, sensory/kinesthetic/embodied ways of knowing, and intersubjective transcendence. We propose that change in the creative arts therapies is driven more by a dynamic system of interactive phenomena the varying combinations of which create conditions for relational attunement, imagination, dialectical tensions and creative resolutions, and the ultimately creative transformation.